Analisis Nilai-Nilai Budaya dalam Lagu Kinanti – Dhat KKN di Desa Penari: Kajian Antropolinguistik - Peber Gustina Hia (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to explain the cultural values ​​contained in the Kinanti – Dhat song, which is the original soundtrack (OST) of the film KKN di Desa Penari. This song was chosen because it contains strong Javanese cultural elements and has a symbolic meaning that is closely related to the film's story. This study uses an anthropolinguistic approach with a qualitative descriptive method. Data were analyzed through text studies and cultural contexts to reveal the hidden meanings in the song lyrics. The results of the study indicate the existence of cultural values ​​that reflect beliefs in supernatural powers and ancestral spirits, the importance of maintaining balance in life, and awareness of ethics, morals, and social norms. In addition, this song also conveys teachings to always be vigilant, protect oneself from bad influences, and uphold local traditions. These findings indicate that the Kinanti – Dhat song not only has aesthetic value, but is also full of cultural values ​​that are important to understand and preserve.